Characterization of neuroinflammatory positron emission tomography biomarkers in chronic traumatic encephalopathy. Issue 1 (3rd February 2022) - Varlow, Cassis; Knight, Ashley C.; McQuade, Paul; Vasdev, Neil
Abstract: Chronic traumatic encephalopathy is a neurological disorder associated with head trauma and is confirmed upon autopsy. PET imaging of chronic traumatic encephalopathy may provide a means to move towards ante-mortem diagnosis and therapeutic intervention following brain injuries. Characterization of the neuroinflammatory PET biomarkers, 18 kDa translocator protein and monoamine oxidase-B was conducted using [ 3 H]PBR-28 and [ 3 H]L-deprenyl, respectively, in post-mortem chronic traumatic encephalopathy brain tissue. [ 3 H]PBR-28 displayed high specific binding in both chronic traumatic encephalopathy (95.40 ± 1.87%; n  = 11 cases) and healthy controls (89.89 ± 8.52%, n  = 3 cases). Cell-type expression of the 18 kDa translocator protein was confirmed by immunofluorescence to microglia, astrocyte and macrophage markers. [ 3 H]L-deprenyl also displayed high specific binding in chronic traumatic encephalopathy (96.95 ± 1.43%; n  = 12 cases) and healthy controls (93.24 ± 0.43%; n  = 2 cases), with the distribution co-localized to astrocytes by immunofluorescence. Saturation analysis was performed to quantify the target density of the 18 kDa translocator protein and monoamine oxidase-B in both chronic traumatic encephalopathy and healthy control tissue. Using [ 3 H]PBR-28, the target density of the 18 kDa translocator protein in healthy controls was 177.91 ± 56.96 nM ( n  = 7 cases; mean ± standard deviation); however, a highly variable target density (345.84 ± 372.42 nM; n  = 11 cases; mean ± standard deviation) was measured in chronic traumatic encephalopathy. [ 3 H]L-deprenyl quantified a monoamine oxidase-B target density of 304.23 ± 115.93 nM ( n  = 8 cases; mean ± standard deviation) in healthy control tissue and is similar to the target density in chronic traumatic encephalopathy tissues (365.80 ± 128.55 nM; n  = 12 cases; mean ± standard deviation). A two-sample t -test determined no significant difference in the target density values of the 18 kDa translocator protein and monoamine oxidase-B between healthy controls and chronic traumatic encephalopathy ( P  > 0.05), albeit a trend towards increased expression of both targets was observed in chronic traumatic encephalopathy. To our knowledge, this work represents the first in vitro characterization of 18 kDa translocator protein and monoamine oxidase-B in chronic traumatic encephalopathy and reveals the variability in neuroinflammatory pathology following brain injuries. These preliminary findings will be considered when designing PET imaging studies after brain injury and for the ultimate goal of imaging chronic traumatic encephalopathy in vivo . Abstract : Varlow et al. report the first in vitro evaluation of PET imaging biomarkers for neuroinflammation in chronic traumatic encephalopathy. High variability in neuroinflammatory pathology target density was found in chronic traumatic encephalopathy compared with healthy controls. In vivo imaging of neuroinflammatory biomarkers in brain injuries is warranted. Graphical Abstract: Graphical Abstract